Building Locally Led Agricultural Policy Analysis Capacity in Africa - Jayne, Thomas S. (2022)
Thomas S. Jayne POLICY SEMINAR Strengthening policy research and analysis capacity: The role of institutional development programs JUL 21, 2022 - 9:00 TO 10:30AM EDT